2019
DOI: 10.3171/2019.3.focus1963
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Gamma Knife radiosurgery for skull base meningiomas: a single-institution experience

Abstract: OBJECTIVEGamma Knife radiosurgery (GKRS) has been successfully used for the treatment of intracranial meningiomas given its steep dose gradients and high-dose conformality. However, treatment of skull base meningiomas (SBMs) may pose significant risk to adjacent radiation-sensitive structures such as the cranial nerves. Fractionated GKRS (fGKRS) may decrease this risk, but until recently it has not been practical with traditional pin-based systems. This study reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 48 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…While single-fraction treatment of small lesions is both effective for controlling tumors and sparing OARs, it can be a considerable challenge to balance tumor control and radiation-induced toxicity for larger tumors, especially skull base tumors. Hypofractionated Gamma Knife Radiosurgery (e.g., 25 Gy in 5 fractions) can optimize said balance of tumor control and normal tissue toxicity in comparison to single-fraction radiosurgery [ 40 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…While single-fraction treatment of small lesions is both effective for controlling tumors and sparing OARs, it can be a considerable challenge to balance tumor control and radiation-induced toxicity for larger tumors, especially skull base tumors. Hypofractionated Gamma Knife Radiosurgery (e.g., 25 Gy in 5 fractions) can optimize said balance of tumor control and normal tissue toxicity in comparison to single-fraction radiosurgery [ 40 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we devised our protocol on the basis of the few studies in the literature that reported favorable outcomes in treating intracranial tumors (26,27). The reported number of fractions ranged from 3 to 5, and the between-fraction time interval from days to months, depending on the center experience and lesion characteristics (28). In our cohort, we delivered 3 or 5 GKRS fractions per-patient, with a median dose of 6 Gy (range=4.7-6.7 Gy), which has been correlated with good tumor control (27).…”
Section: Discussionmentioning
confidence: 99%
“…4 However, our study is unique because we evaluated a novel mcfSRT system and demonstrated dosimetric feasibility in the setting of conventionally fractionated treatment. Prior reports of using the Leksell Gamma Knifeâ Icon TM for fractionated radiotherapy have been limited to short courses of RT over 5 fractions or less; [14][15][16][17] there are no known published reports of treatment courses over prolonged fractionation schedules using this device, though retrospective work to evaluate such treatments is ongoing (Dr Michael Yan, 2022, personal communication).…”
Section: Discussionmentioning
confidence: 99%